WELCOMING THE ISLAMIC EDUCATION REVOLUTION: ADAPTIVE CURRICULUM IN FACING THE DIGITAL ERA - Machmud Yunus; Deni Supriad; Nina Siti Kurniati; Didin Solehudin (Yayasan Haiah Nusratul Islam, 2025)
The development of information and communication technology in the digital era has had a significant impact on various aspects of life, including in the world of Islamic education. This transformation requires curriculum adjustments that not only maintain the values of Islamic teachings, but are also able to adapt to the needs of the times. This article aims to review and analyze the development of an adaptive Islamic education curriculum amidst the dynamics of the digital era. This study uses a descriptive-qualitative method based on literature studies, by reviewing various relevant literature related to the basic concepts of the curriculum, the principles of Islamic education, and the integration of technology in learning. The results of the study show that the development of Islamic education curriculum in the digital era cannot be done partially, but requires a holistic and collaborative approach. The involvement of various parties, such as educational institutions, government, and society is very necessary to create a relevant and contextual curriculum. The implementation of an online learning platform is one of the strategic solutions to improve the accessibility, quality, and efficiency of Islamic religious learning, especially in remote areas.